Which of the following equations is equivalent to 3(2p + 4) – (3p – 4) = 43? 3p + 8 = 43 3p + 16 = 43 2p + 8 = 43

Question

Which of the following equations is equivalent to 3(2p + 4) – (3p – 4) = 43?
3p + 8 = 43
3p + 16 = 43
2p + 8 = 43
2p + 16 = 43

in progress 0
Eliza 2 months 2021-10-14T07:55:57+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-10-14T07:57:49+00:00

    Answer:

    3p+8=43

    Step-by-step explanation:

    6p+12-3p-4=43

    3p+8=43

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )